CONTINUOUS TECHNOLOGICAL CHANGE AS A CHALLENGE FOR CONTEMPORARY LABOUR LAW - Midžović, Milica (Zbornik radova Pravnog fakulteta u Novom Sadu, 2026)
The technological transformation of work constitutes one of the central challenges of contemporary labour law. The digitalisation of work processes, the expansion of flexible forms of work engagement, and the increasingly widespread use of artificial intelligence systems and algorithmic management are bringing about profound changes in the way work is organised, supervised, and evaluated. These developments do not merely affect the structure of the labour market; they directly reshape the legal status of employees, calling into question traditional labour-law institutions and existing mechanisms of legal protection. This paper analyses the impact of technology-driven changes on the employment relationship, with particular emphasis on algorithmic management, automated decision-making, and digital forms of workplace monitoring. Special attention is devoted to identifying the risks these processes pose to the effective protection of fundamental labour and human rights, as well as to legal certainty within the employment relationship. Building on a normative and theoretical analysis of the applicable legislation of the Republic of Serbia, the paper examines the extent to which the existing legal framework is capable of responding to the challenges of technological transformation. In a comparative perspective, relevant European standards and contemporary regulatory trends are also considered, with the aim of identifying legal gaps and formulating de lege ferenda recommendations designed to strengthen employee protection and preserve a fair balance between technological progress and the core values of labour law.
Keywords: digital transformation of work; employment relationship; labour market; algorithmic management; labour law of the Republic of Serbia.